2002
DOI: 10.1142/s0218216502001743
|View full text |Cite
|
Sign up to set email alerts
|

A Computation of Superbridge Index of Knots

Abstract: Abstract. We show that the list {3 1 , 4 1 , 5 2 , 6 1 , 6 2 , 6 3 , 7 2 , 7 3 , 7 4 , 8 4 , 8 7 , 8 9 } contains all 3-superbridge knots. We also supply the best known estimates of the superbridge index for all prime knots up to nine crossings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In particular, Jeon and Jin [6] conjectured that the only knots with superbridge index 3 are the trefoil knot and the figure eight knot. This conjecture would be proved if it could be shown that the trefoil knot and the figure eight knot are the only non-trivial knots with conformations such that the binotrix does not intersect itself or the anti-binotrix and the bridge map realizes a value of 4 in such a conformation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Jeon and Jin [6] conjectured that the only knots with superbridge index 3 are the trefoil knot and the figure eight knot. This conjecture would be proved if it could be shown that the trefoil knot and the figure eight knot are the only non-trivial knots with conformations such that the binotrix does not intersect itself or the anti-binotrix and the bridge map realizes a value of 4 in such a conformation.…”
Section: Discussionmentioning
confidence: 99%
“…We have proved that the spaces P 3 and P 4 are path connected, so in general, we would like to conjecture the following: Proof. Suppose e = (e 1 , e 2 , e 3 ) be an arbitrary element in the set {−1, 1} 3 . By corollary 3.7.1, an element φ ∈ A 4 given by t → (e 1 t 2 + a φ t, e 2 t 3 + b φ t, e 3 t 4 + c φ t) is an embedding if and only if 3a 2 φ + 4e 2 b φ > 0 or e 1 a 3 φ + 2e 1 e 2 a φ b φ + e 3 c φ = 0.…”
Section: By Proposition 26 It Is Easy To See That the Setmentioning
confidence: 99%
“…We conjecture that there are no 5 crossing knots in degree 6. This will be more clear once the superbridge index of all the possible 3-superbridge knots in the list of Jin and Jeon [3] is completely known. We show that all 5 crossing knots and all 6 crossing knots (including the composite knots) are realized in degree 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This list of 12 knots contains all the 3-superbridge knots. Details behind the selection of 12 knots and the rejection of 35 knots will be handled in [6].…”
Section: Prime Knots Up To 9 Crossingsmentioning
confidence: 99%